Aspen Plus modelling of the MILENA dual fluidised bed biomass gasifier technology - Mohadeseh Naderi; Hamid Rashidi; Anthony Reynolds; Wayne Doherty (International Journal of Thermofluids, 2025)
The Energy Research Centre of The Netherlands is developing MILENA gasification technology to convert biomass fuels into high-value gaseous and liquid products. MILENA is a steam-blown dual fluidised bed (DFB) gasification process with separate gasification and combustion zones. This DFB gasifier produces high-quality gas with low N2 content suitable for vehicle fuel or natural gas grid injection. This study presents a semi-kinetic Aspen Plus model for MILENA gasification, including stages like drying, rapid pyrolysis, gasification, combustion, and tar cracking and reforming. Pyrolysis as a key step, was modelled using experimental data for the rapid pyrolysis of wood to calculate the yields of gases, char and tar. The gasification step is modelled as a continuous stirred-tank reactor (CSTR) and considers reaction kinetics. The simulation results, including product gas composition, mass flow rate, and tar concentration, were validated against experimental data for the MILENA gasifier, showing very good agreement. A low relative error of 0.39 % was the lowest for H2 and 4.17 % was the highest for CO2 in product gas composition, validating the model’s accuracy. The lower heating value (LHV) of the dry gas mixture was calculated. Sensitivity analyses demonstrated that H2 increases with moisture content, supporting the role of the water gas shift (WGS) reaction. Additionally, variations in STBR significantly affect the gas composition.